Pengaruh Kontribusi Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan Bermotor Terhadap Pendapatan Asli Daerah Pada Badan Pendapatan Daerah Provinsi Lampung Tahun 2018 - 2022 - Muhammad Ravi Pratama; Darwin Warisi; Maria Septijantini Alie (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to determine the effect of motor vehicle tax contribution and motor vehicle name return duty on the original revenue of Lampung Province. The method used in this study is quantitative descriptive where the data processing is carried out statistically. The data used in this study are secondary. The number of samples is 60 months using the Saturated Sampling method, a group of Non-Probability Sampling, which is carried out by census where the population is sampled, namely reports on the realization of motor vehicle taxes, motor vehicle name return duties, and local original income for 2018-2022. Analysis techniques are carried out through classical assumption tests, multiple linear regression tests, and hypothesis tests. Based on the results of the analysis, it can be concluded that simultaneously motor vehicle tax, and motor vehicle name return duty have a positive and significant effect on local original income, and partially each variable has a significant positive effect on regional original income.